Investigating the roles of destination image and place attachment in determining residents’ pro-tourism behaviour in Kuching City / Sherrymina Kichin - Kichin, Sherrymina (2022)
In today’s competitive environment, many tourism businesses focus on effective branding as a part of their destination marketing strategy. As such, destination image is acknowledged as a powerful tool for tourism and as an important indicator to increase flow of tourists to a destination. Nonetheless, perspectives of residents which constantly be regarded as one of the most important stakeholders in tourism destinations’ sustainability tend to be largely overlooked by the researchers. On top of that, little attention has been given on how the residents’ attachment to a particular place could contributes to better image perceptions and subsequently, influences their pro tourism behaviour. Drawing on Social Exchange Theory and Internal Branding Theory, this study took a broader perspective to investigate moderation effect of place attachment towards the relationship between destination image (cognitive-affective-conative-unique) and pro tourism behaviour among residents in Kuching, Sarawak. The study adopted a quantitative approach via the use of hardcopy and online questionnaires. Total sample size of 300 were selected using purposive sampling technique. PLS-SEM was performed using SmartPLS 3.0 to analyse the data. The study findings have answered three (3) research objectives. The first objective is to investigate the residents’ perception towards the destination image of Kuching as a tourism destination. The study revealed that Kuching is highly perceived in terms of its conative image, followed by unique image, cognitive image, and affective image by its residents. The second objective is to examine how does Kuching destination image (cognitive-affective-conative-unique) influence the residents’ pro-tourism behaviour. The result revealed that the four holistic components were significantly and positively predicted the residents’ pro-tourism behaviour. Lastly, the third objective is to examine whether place attachment moderates the effect of destination image (cognitive-affective-conative-unique) on the residents’ pro-tourism behaviour. The study finding found out that the place attachment moderates the effect of affective and conative image on the residents’ pro-tourism behaviour. Nonetheless, it is revealed that the place attachment does not moderate the effect of cognitive and unique image on the residents’ pro-tourism behaviour. Ultimately, the research novelty contributes to tourism discipline in which it lies on the study abilities to come out with clear and holistic destination image from the residents’ perspectives as well as understanding on the notion of how place attachment could influence the residents to perceive the destination image and subsequently, contribute to their pro-tourism behaviour. As such, relevant government agencies and tourism practitioners could come out with effective initiatives that could foster behavioural change among the residents to be a pro-tourist, improve destination marketing of Kuching through brand image formation while sustaining Kuching as a tourist destination via the roles of residents.